2015
DOI: 10.1111/josh.12245
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism, Educational Plans, and Anxiety Among Children With Incontinence and Their Parents

Abstract: Absenteeism contributes to familial anxiety and educational difficulties. Despite the potential for educational plans to support these children at school, these plans are underutilized for children with incontinence. This population requires more attention to their academic and social-emotional well-being at school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Participants commonly reported that their lessons were disrupted due to frequent toilet visits and those with severe daytime continence problems reported leaving the classroom 3 or 4 times during a lesson to use the toilet. This finding is consistent with other studies on school experiences in young people with continence issues and other chronic health conditions which report higher rates of absenteeism in these populations (Filce & LaVergne, , ; Sato et al ., ; Wodrich & Cunningham, ). Absenteeism, even for part of a lesson, creates reduced opportunities for learning, asking questions, and teacher contact.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Participants commonly reported that their lessons were disrupted due to frequent toilet visits and those with severe daytime continence problems reported leaving the classroom 3 or 4 times during a lesson to use the toilet. This finding is consistent with other studies on school experiences in young people with continence issues and other chronic health conditions which report higher rates of absenteeism in these populations (Filce & LaVergne, , ; Sato et al ., ; Wodrich & Cunningham, ). Absenteeism, even for part of a lesson, creates reduced opportunities for learning, asking questions, and teacher contact.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study align closely with previous work conducted outside the United Kingdom on the experiences of school children with continence problems. These individuals all report less than satisfactory toilet conditions, conflicting rules regarding toilet access, and trepidation in disclosing their problem to teachers (Filce & LaVergne, ; Lundblad & Hellstrom, ; Lundblad et al ., ). However, in addition to previous work, it highlights the social and academic challenges faced by this group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-confidence and achievement motivation are undermined. (p. 395) These effects are frequently exacerbated by learning difficulties, as children with chronic medical conditions or special health care needs endure multiple short-term and long-term issues that adversely affect their ability to learn (Filce & LaVergne, 2015;Forrest, Bevans, Riley, Crespo, & Louis, 2011). According to Clay (2004), approximately 20% of children have a chronic illness and, for at least one-third of these, the illness is significant enough to negatively impact normal educational progress.…”
Section: Introductionmentioning
confidence: 99%